Consequences of smoking during pregnancy for mother and child - Marín, Gustavo Horacio (2003)
Objective: to evaluate the consequences of maternal smoking. Methods: a prospective study of 1.103 pregnant women. A survey in the state Hospital San Martin, de La Plata, Buenos Aires determined general data. Newborn and placenta data were also reported. Mother and child cord samples were obtained to determine blood elements and flow cytometry analysis of lymphocyte subsets performed. Data from smoking (S) and non-smoking (NS) groups were evaluated through relative risk, chi square and Student's t test. Results: of all patients, 887 were NS and 226 said they smoked over five-cigarettes/day (S). The S group showed a higher probability of premature deliveries when compared to the NS group, with newborns weighing under 2,5kg, small in relation to gestational age, with Apgar scores at the 5th minute under six and hyaline membrane syndrome; intrauterine death risk was higher in this group who attended less medical appointments than scheduled. Umbilical cord blood analysis indicated lower reticulocyte index for S mothers, neutrophil count and CD4/CD8 ratio and increased erythroblast, eosinophil, basophil, total and CD8+T lymphocyte counts. Conclusions: data could explain the observations by other authors related to an increased incidence of allergy and infections in newborns caused by maternal smoking.